Determinan Determinan Kecurangan Laporan Keuangan Menggunakan Teori Fraud Pentagon Dengan Komite Audit Sebagai Variabel Moderasi - Suganda, Nurdiyanti (APSSAI ACCOUNTING REVIEW, 2024)
This research aims to examine and analyze the determinants of financial reporting using the theory of fraud pentagon with the audit committee as the moderating variable. The research sample consisted of 26 companies for five years; thus, the number of companies was 130. Data analysis technique for panel data regression model using WarpPLS 7. The results of this study state that opportunity and rationalization affect financial statement fraud. pressure, ability, and arrogance do not affect the financial statements. The audit committee can moderate the effect of opportunity on financial statement reporting. In contrast, the audit committee on the financial statements cannot moderate the influence of pressure, rationalization, ability, and arrogance.